Engineering Education Vis-a-Vis Emerging Free Global Market - Wakhlu, O. N. (Journal of Engineering Education Transformations, 1993)
Implications of a Global Market The world has undergone a revolutionary change, recently. The most important development is that the world has become one global free market. The global market is characterised by the presence of three basic factors, namely: 1) competition, 2) constant change, and 3) customer’s control and contentment.